Encapsulamento de compostos orgânicos voláteis em matrizes biopoliméricas para o controle de insetos pragas - Aguiar, Maria Clara Santana (Universidade Federal de São Carlos, 2017)
Traditional pesticides were introduced to the agriculture in order to control pests, which are harmful to the crops. However, this indiscriminate use of synthetic pesticides has been causing environmental disorders, and promoting the development of alternative products such as essential oils. Nevertheless, these compounds are made of usually unstable molecules, which are easily degradable, or lost. In this sense, there is necessity to develop specific alternatives to their use in the field. The formulation of capsules in nano- or micrometric scale is an alternative for efficient use of essential oil, what may increase its stability, and residual period. In this context, this project aimed to develop, characterize and evaluate the biological activity of nano/micro particles in powder loaded with orange essential oil. The process to obtain microparticles was developed by Spray Dryer to encapsulate the volatile in a core material. Gelatin and Lignin were used as biopolymers. The quantification of the essential oil content (encapsulated and absorbed) was done by headspace extraction with a simultaneous analysis in a gas chromatograph coupled to a flame ionization detector. The method was validated according to the main figures of merit (selectivity, linearity, precision, accuracy, detection and quantity limit). The calibration curves also were evaluated investigation possible matrix effect. The results showed that the transfer velocity of the sample in Spray Dryer was the main factor for encapsulament efficiency for both biopolymers. The best conditions presented drying efficiency of 44% and 72% for gelatin and lignin, respectively, of mass from the final product. The encapsulement efficiency ranged between 320 and 900 mg g-1 for gelatin, and from 200 to 309 mg g-1 for lignin, considering the essential oil/polymer ratio. All the samples were submitted to several physicochemical characterization parameters. Scanning electron microscopy was used to evaluated the morphology and surface of the products. The microparticles showed a micro spherical rough formation, with a heterogeneous distribution of size, smooth surface (gelatin), or with fissures (lignin). Studies of controlled release in aqueous media were performed by headspace extraction. The micro particles with wider rate of polymer related to essential oil showed a retention of the volatile fraction 10.9 and 1.87 times higher for the gelatin products and lignin, respectively. Similar results were obtained in the thermal degradation analysis. In this step, the products were kept at 40°C in range of to 90 min followed by headspace extraction. It was observed that gelatin and lignin micro particles are efficient to protect against lost by volatilization, and consequent, to increase of life time for the essential oil. Finally, the formulated products were submitted to bioassays against Spodoptera frugiperda, which is the main pest of the corn crop. The presence of such products in the larval diet produced an increase in consumption and the initial growth rate. However larval and pupal mortality, pupal malformation, leakage attempts from the system and absence of egg scales (protection against natural enemies) were observed. The results of this project showed gains in stability, that they were able to be dispersed in aqueous medium, and remained active to the control of Spodoptera frugiperda.
Encapsulation of volatile organic compounds in matrices biopolymeric for insect pests control
Keywords: Microencapsulamento; Citros; Óleo essencial; Spodoptera frugiperda; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS